2020
DOI: 10.21621/sajms.2020141.01
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personal and Cultural Factors on Green Buying Intentions with Mediating Roles of Environmental Attitude and Eco-Labels as Well as Gender as a Moderator

Abstract: The purpose of this paper is to examine the impact of personality traits of consumers regarding their green buying intention by measuring the mediation effects of eco-labels and environmental attitude along with the moderation of gender. To the researchers' best knowledge, there is a lack of research in developing countries in explaining influence of rarely researched factor such as loyalty proneness on green buying intention. To uncover this gap, using survey method data from a sample of 434 has been collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Additionally, there is a clear conviction that consumption values are multidimensional independent variables. Multidimensional models in customer values portray better accuracy in purchase prediction, especially when it is coupled with positive word-of-mouth, compared to singular dimension model [29,30]. Along the same notion, positive wordof-mouth is included.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, there is a clear conviction that consumption values are multidimensional independent variables. Multidimensional models in customer values portray better accuracy in purchase prediction, especially when it is coupled with positive word-of-mouth, compared to singular dimension model [29,30]. Along the same notion, positive wordof-mouth is included.…”
Section: Methodsmentioning
confidence: 99%
“…Yeşil satın alma yazını incelendiğinde araştırmacıların, tüketicilerin yeşil satın alma davranış ve niyetlerini farklı değişkenler çerçevesinde ele aldıkları görülmektedir. Söz konusu olgular hakkında yapılan yakın zamanlı çalışmalar, tüketicilerin etik algıları (Başgöze, 2012), algılanan çevresel sorumluluk (Zheng vd., 2020), yeşile boyama, yeşil marka imajı ve yeşil marka sadakati (Çavuşoğlu, 2021), yeşil marka değerlendirmesi ve yeşil reklam etkileşimi (Mansoor vd., 2022), çevresel değerler (Temizkan, 2022) yeşil satın alma davranışı ile; tüketici kişiliği ve etik inançları (Lu, Chang ve Chang, 2015), görünüş bilinci, tüketim ve fiyat (Chunling vd., 2019), kişisel ve kültürel faktörler, çevresel tutum, eko-etiket ve cinsiyet (Hasnain, Raza ve Qureshi, 2020), dışa dönüklük ve yeşil reklama yönelik tutumlar (Altuğ, Özhan ve Meco, 2020), yeşil ürün tutumu (Yıldız ve Kütahyalı, 2021), davranışsal niyet ve kontrol inançları (Çıvgın ve Kızanlıklı, 2022), çevresel tutum ve yükselen ekonomi (Kaur, Gangwar ve Dash, 2022) yeşil satın alma niyeti ile ilişkilendirilmiştir.…”
Section: Yeşil Satın Almaunclassified
“…They found that gender serves as a moderator of the relationship between environmental attitude and green buying intention, and a significant interactional effect of environmental attitudes and gender. They suggest that females are more inclined toward green buying intention based on their positive environmental attitudes and positive perception of the ecolabels (Hasnain et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%